Perawatan saluran akar satu kali kunjungan dilanjutkan dengan restorasi endocrown - Rosita Stefani (Jurnal Kedokteran Gigi Terpadu, 2023)
Introduction: Root canal treatment is a common procedure in dentistry. The main indications for root canal treatment are irreversible pulpitis and pulpal necrosis resulting from a carious process, fracture, or trauma to the tooth. The success of root canal treatment depends on various factors, one of which is post-endodontic restoration. Objective: This case report aims to demonstrate a one-visit root canal treatment followed by endocrown restoration. Case report: A 22-year-old male patient came with complaints of throbbing tooth pain in the lower right side since 1 week ago. Intra oral examination of tooth 46 showed a temporary filling on the occlusal surface. Radiographic findings showed that the crown had a radiopaque appearance reaching the pulp chamber, without periapical abnormalities. Root canal treatment was performed based on the diagnosis of irreversible pulpitis followed by endocrown restoration. Root canal treatment begins with mandibular block anesthesia and then inserts a rubber dam, opens the cavity, explores the root canal, and prepares the root canal. Biomechanical preparation was carried out using a single length technique, combined with 5.25% NaOCl irrigation, 17% EDTA, and 2% chlorhexidine. Root canal closure was performed in single visit, with the warm vertical condensation technique. The next restoration was carried out one week after root canal treatment, with an endocrown. A week later the patient came for control with no complaints. Conclusion: Root canal treatment in single visit followed by endocrown restoration was successfully carried out.